2016
DOI: 10.1371/journal.pone.0149545
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-Associated Microbiome Correlates with Pollution Parameters and the Allergenicity of Pollen

Abstract: Pollen allergies have been rapidly increasing over the last decades. Many allergenic proteins and non-allergenic adjuvant compounds of pollen are involved in the plant defense against environmental or microbial stress. The first aim of this study was to analyze and compare the colonizing microbes on allergenic pollen. The second aim was to investigate detectable correlations between pollen microbiota and parameters of air pollution or pollen allergenicity. To reach these aims, bacterial and fungal DNA was isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 60 publications
2
72
0
1
Order By: Relevance
“…While pollen-associated fungi were extensively investigated, only a few studies focused on bacteria. However, these studies relied only on the cultivated fraction (Colldahl and Nilsson, 1973), amplicon libraries sequencing (Junker and Keller, 2015) or molecular fingerprinting (Obersteiner et al, 2016). Here, for the first time, cultivation-dependent, cultivation-independent and microscopy analysis of four different pollen species were performed, thus achieving the most comprehensive bacterial microbiota analysis of pollen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While pollen-associated fungi were extensively investigated, only a few studies focused on bacteria. However, these studies relied only on the cultivated fraction (Colldahl and Nilsson, 1973), amplicon libraries sequencing (Junker and Keller, 2015) or molecular fingerprinting (Obersteiner et al, 2016). Here, for the first time, cultivation-dependent, cultivation-independent and microscopy analysis of four different pollen species were performed, thus achieving the most comprehensive bacterial microbiota analysis of pollen.…”
Section: Discussionmentioning
confidence: 99%
“…It could be shown that insect-pollinated pollen has a more lipid-rich coat than wind-pollinated pollen (Edlund et al, 2004). Bacterial and fungal patterns on different pollen species (birch and timothy grass) were found to be species-specific, and the birch pollen showed higher microbial diversity than timothy grass (Obersteiner et al, 2016). However, these two pollen species have been collected from different regions, while in our work we analysed samples originating from four sampling sites within a restricted geographic area, with different pollen species sampled from the same sites.…”
Section: Cultivation-independent Analysis Of Bacterial Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Many research has been focused on pollen-food allergy syndrome (PFAS), including pollenassociated microbiome correlates with pollution parameters and the allergenicity of pollen. [18][19][20][21][22][23][24] Whether aspartyl proteases from plant flowers could degrade the epithelial cells in the mucus layers in human nasal cavity, lung, mouth, and intestine remains unknown. The precise molecular mechanism for the degradation of human epithelial cells caused by plant aspartyl proteases warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of planning in the design of urban spaces with low species biodiversity at planting, overabundance of species acting as pollen sources, exotic species prompting new allergies in the population, botanical sexism, the presence of invasive species, inappropriate garden management and maintenance activities, cross‐reactivity between phylogenetically related species and the interaction between pollen, its microbiome, and air pollutants are major causes triggering pollen allergy . In recent decades, city planning strategies have favored pollen‐producing male bushes, trees, and plants.…”
Section: Framing the Issuementioning
confidence: 99%